2019
DOI: 10.1177/1836939119855562
|View full text |Cite
|
Sign up to set email alerts
|

Early years teachers’ perspectives on the effects of NAPLAN on stakeholder wellbeing and the impact on early years pedagogy and curriculum

Abstract: National Assessment Program for Numeracy and Literacy (NAPLAN) is the national assessment programme for literacy and numeracy in Australia administered to children in Years 3, 5, 7 and 9 each year. The testing process was introduced in 2008 and is described by the developers as low stakes, however, research has highlighted that this is not the case. This paper examines the perceptions of teachers in the early years of school on the impact NAPLAN has on wellbeing of stakeholders, and the pedagogy and curriculum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In Australia, the pushed down curriculum and expectations for academic achievement has led to a decrease in play based pedagogies (Barblett et al, 2016; Hesterman & Targowska, 2020), with teachers also reporting limiting children’s contributions to the curriculum (Leggett & Ford, 2013). High-stakes testing such as NAPLAN also imposes on pedagogy with reports that teachers spend more time on subjects that are assessed (Roberts et al, 2019). This trend known as ‘schoolification’ has been documented internationally and led to significant changes in early childhood pedagogy, due to conceptions of quality practice being cast as only those that can be measured and evaluated (Palaiologou & Male, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Australia, the pushed down curriculum and expectations for academic achievement has led to a decrease in play based pedagogies (Barblett et al, 2016; Hesterman & Targowska, 2020), with teachers also reporting limiting children’s contributions to the curriculum (Leggett & Ford, 2013). High-stakes testing such as NAPLAN also imposes on pedagogy with reports that teachers spend more time on subjects that are assessed (Roberts et al, 2019). This trend known as ‘schoolification’ has been documented internationally and led to significant changes in early childhood pedagogy, due to conceptions of quality practice being cast as only those that can be measured and evaluated (Palaiologou & Male, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since its inception, there has been widespread criticism of NAPLAN as high stakes tests can have a negative impact on pedagogy, curriculum, and the stress levels of students and teachers (Cumming et al, 2016;Roberts et al, 2019). Researchers have argued that "teaching to the test" has become a part of teachers' practice within the classroom and the focus of the curriculum has narrowed to the specific outcomes that are expected to be tested (see .…”
Section: Problems With Naplan Census Testingmentioning
confidence: 99%
“…Although some have argued that the change to accountability structures has been beneficial, and perhaps even necessary for the teaching profession, others have suggested that test-based accountability only serves to "narrow" the curriculum and bring the commencement of formal schoolwork to earlier years of schooling (Gable & Lingard, 2015;Roberts et al, 2019). This can result in students having to "grow up fast" as they are forced to cope with more rigid and formal learning.…”
Section: Problems With Naplan Census Testingmentioning
confidence: 99%
“…Biesta [3] argues that contemporary measures of quality education focus on academic achievement across a controversially small and selective number of domains and subject areas, often privileging literacy and numeracy over children's social and emotional wellbeing. Within the domain of literacy, the focus on academic achievement has also led to problematic repercussions for children's early reading development, narrowly defining 'reading' as the ability to achieve the expected outcomes that are assessed via standardized tests [4], for younger and younger age groups [5]. Framed within this problematic discourse, our study sought to investigate how a teacher may circumvent such narrow and limiting expectations-expectations that would fail to address the diverse needs and potential of every child and ensure equity and access for all children.…”
Section: Introductionmentioning
confidence: 99%
“…There is no question that assessments are useful tools for teachers when planning for teaching and learning [6]. However, in light of research that has found that some teachers teach to the test [4,5], with some early childhood educators targeting specific readingrelated outcomes in isolation [7], there is concern that pressure to ensure that children (and schools) will perform well in national literacy tests may devolve the teaching and learning of reading into a narrow objective to meet particular reading outcomes, 'readying' children from a younger and younger age to meet expected outcomes in their future schooling. We argue that such an objective is one that adopts a narrow, grade-age-centric approach to teaching that fails to account for and address the diverse needs and potential of every child, which may also lead to an increase in the achievement and equity gaps that are present in current K-12 education.…”
Section: Introductionmentioning
confidence: 99%